Risk Factors for Knee Stiffness Surgery After Tibial Plateau Fracture Fixation. Issue 9 (September 2018) - Reahl, G. Bradley; Marinos, Dimitrius; O'Hara, Nathan N.; Howe, Andrea; Degani, Yasmin; Wise, Brent; Maceroli, Michael; O'Toole, Robert V.
Abstract : Objective: To determine the risk factors for knee stiffness surgery after tibial plateau fixation. Design: Retrospective observational cohort study. Setting: Academic Level I trauma center. Patients/Participants: A study group of 110 patients who underwent knee stiffness surgery (manipulation while under anesthesia, arthroscopic lysis of adhesion, or quadricepsplasty) at a time remote from open reduction and internal fixation of tibial plateau fractures and a control group of 319 patients with tibial plateau fractures treated with open reduction and internal fixation who did not undergo knee stiffness surgery and who had either a minimum of 1 year of follow-up or clearly documented range of motion ≥110 degrees with a minimum of 90 days of follow-up. Intervention: Each case was assessed from the time of index admission through study event, end of minimum follow-up, or achievement of ≥110 degrees range of motion. Main Outcome Measurements: Knee stiffness surgery. Results: Total number of weeks in an external fixator (odds ratio, 1.5 per week; 95% confidence interval, 1.3–1.7; P < 0.001) and the presence of bilateral tibial plateau fractures (odds ratio, 3.3; 95% confidence interval, 1.2–9.1; P = 0.02) were significant predictors of knee stiffness intervention. Conclusion: Clinicians should be aware that the time spent in external fixation and the presence of bilateral tibial plateau injuries are strong risk factors for requiring subsequent surgery to treat knee stiffness. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.